Power of lower extremities and age were the main determinants on the agility test for adults in a cohort of men aged 66–91 years. (4th March 2021) - Manderoos, Sirpa; Wasenius, Niko S.; Laine, Merja K.; Kujala, Urho M.; Mälkiä, Esko A.; Kaprio, Jaakko; Sarna, Seppo; Bäckmand, Heli M.; Kettunen, Jyrki A.; Aunola, Sirkka; Eriksson, Johan G.
Abstract: Study Design: Cross-sectional study. Objective: To evaluate the relationship between agility and personal factors, muscle strength and power, mobility, self-reported balance and physical activity among older men. Methods: Agility was measured by using the Agility Test for Adults (ATA). We studied 100 Finnish male former elite athletes (endurance n = 50; power n = 50) and 50 matched controls aged 66 to 91 years (mean age 75.5 years). The associations between agility and other variables were similar between three groups; thus, multiple linear regression analyses were done by using the pooled data of the participants. Results: On the basis of multiple linear regression analyses, combination of age ( p = .02), self-reported Activities-specific Balance Confidence scale (ABC scale), jumping height ( p = .001) and self-rated health explained 26% of the variance in execution time of ATA (R 2 = 0.26; p = .000002) among elderly men. Conclusion: Power of lower extremities and age were the main determinants of the results of ATA in a cohort of men aged 66–91 years. From a clinical point of view, power of lower extremities measured by test demanding explosive power plays an important role to maintain or enhance capacity of agility.